La formación de la curva de rendimientos en nuevos soles en Perú - Rodríguez, Augusto (2002)
The objective of this paper is to analyze the formation process of the Nuevo Sol Yield Curve in Peru, specifically the evolution of  its different terms as a consequence of diverse  internal  and  external policies  and  events. For this purpose, the zero coupon yield curve or spot curve is estimated, based on the Nelson y  Siegel (1987) method. The analysis suggests that  in the Peruvian case the developing yield curve has been sensible  to  internal  events as the issue  of  a  bond  with a maturity longer  than the existing term to maturity, and external events such as foreign interest rates changes. Hence, the yield curve has adopted concave, convex and lineal forms within one and a half year period, without the agents having changed their perceptions about the macroeconomic fundamentals.